Effect of The Pfizer-Biontech Vaccine on Ifn-Γ Serum Levels and its Genetic Variations in Response to Vaccination - Fade, Radhia Hussain; Mohemed Fleeh Dareef; Microbiology, Salah Mehdi Medical (South Eastern European Journal of Public Health, 2024)
Background: Pfizer vaccine, which is a nucleoside-modified mRNA vaccine against coronavirus disease 2019 (COVID-19) is one of the first mRNA products to be approved by the Food and Drug Administration (FDA) and the European Medicines Agency (EMA). Aim of the study: The aim of this study is to study the impact of Pfizer vaccine on the levels of interferon gamma (IFN-γ) serum levels and its gene polymorphism after 3 months and 6 months of vaccination with Pfizer vaccine . Materials and methods: This case-control study involved (150) subjects who were divided into three groups (each group included 50 subjects). The first group included (50) vaccinated group 3 months after second dose of Pfizer vaccine, and the second group included (50) vaccinated group 6 month after second dose of Pfizer vaccine. The third group was the control group which included (50) healthy unvaccinated subjects. The study was done during the period from May /2022 to September / 2022). Serum levels of IFN-γ were estimated by ELISA technique. The PCR technique was used to study gene polymorphism for IFN-γ. Results: The results in figure (1) showed that the mean levels of INF-γ among the male participants (after 3 months of vaccination, after 6 months of vaccinations, and the control group) were (292.54, 231.48, and 15.71), respectively, with highly significant differences (HS) between the three groups (p<0.01). The results also showed that the mean levels of INF-γ among female participants (after 3 months of vaccination, after 6 months of vaccinations, and the control group) were (317.31, 228.14, and 15.74), respectively, with highly significant differences (HS) between the three groups (p<0.01). Analysis of rs2430561 SNP of (IFN-γ) gene using Sanger sequencing. Single “T” peak indicative of a T homozygous allele showed that Single “A” peak indicative of a A homozygous allele. Presence of the “T” and “A” peak indicative of T/A heterozygous allele. Conclusion: Pfizer vaccine was shown to have significant impacts on IFN-γ levels and presence of single T/A alleles is indicative of heterogeneous T/A allele on analysis of rs2430561 SNP of (IFN-γ) gene among vaccinated individuals.